Neonatal Marfan Syndrome - Tognato, Eleonora; Perona, Anna; Aronica, Angela; Bertola, Antonella; Cimminelli, Lina; De Vecchi, Simona; Eshraghy, Mohammad Reza; Loperfido, Bruna; Vivenza, Claudia; Manzoni, Paolo (American Journal of Perinatology, 2019)
Objective The Marfan syndrome (MFS) is an autosomal dominant disorder of connective tissue resulting from pathogenic variants of the fibrillin-1 gene (FBN1) with skeletal, cardiac, and ocular involvement.Study Design We report on a full-term male neonate, who showed at birth characteristics and dysmorphisms suggestive of nMFS, combined with the detection of severe cardiovascular disease. A multidisciplinary team made up of neonatologists and pediatricians, cardiologists, geneticists, ophtalmologists, physiatrists and physioterapists was formed to manage this patient.Results and Conclusion Early diagnosis of this rare condition is critical for adequate treatment and specific follow-up, and impacts significantly on prognosis.
Keywords: neonatal Marfan syndrome; Ghent criteria; severe cardiovascular disease; neonate